2006
DOI: 10.1353/psc.2005.0059
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Climatology of Viti Levu (Fiji) and Current Climatic Trends

Abstract: In this paper we characterize the climate at Nadi and Suva in Fiji from 1961 to the present, providing a picture of ongoing climate trends. The focus is on surface observations of air temperature and rainfall, although some information on South Pacific Ocean climate is also discussed, given its relevance for Fiji. Our findings suggest that surface air temperatures have registered increasing trends at both Suva and Nadi (the two observatory sites in Fiji identified as Weather Observing Stations under the global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 11 publications
(2 reference statements)
2
40
0
Order By: Relevance
“…4°C . A t n a tional level, the annual mean surface air temperature has increased by 1.2 °C since the reliable records began in Fiji, representing a rate of 0.25 °C per decade (Mataki et al, 2006). There was significant increase in the annual number of hot days and warm nights, and significant decrease in the annual number of cool days and cold nights, particularly in years after the onset of El Nino in the period 1961 to 2003 but extreme rainfall trends were generally less spatially coherent than extreme temperatures (Griffiths et al, 2003;Manton et al, 2001).…”
Section: Observed Changes In Climate Trends and Future Projectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…4°C . A t n a tional level, the annual mean surface air temperature has increased by 1.2 °C since the reliable records began in Fiji, representing a rate of 0.25 °C per decade (Mataki et al, 2006). There was significant increase in the annual number of hot days and warm nights, and significant decrease in the annual number of cool days and cold nights, particularly in years after the onset of El Nino in the period 1961 to 2003 but extreme rainfall trends were generally less spatially coherent than extreme temperatures (Griffiths et al, 2003;Manton et al, 2001).…”
Section: Observed Changes In Climate Trends and Future Projectionsmentioning
confidence: 99%
“…There was significant increase in the annual number of hot days and warm nights, and significant decrease in the annual number of cool days and cold nights, particularly in years after the onset of El Nino in the period 1961 to 2003 but extreme rainfall trends were generally less spatially coherent than extreme temperatures (Griffiths et al, 2003;Manton et al, 2001). Mataki et al (2006) also examined the changes in the frequency of extreme temperature events and found that significant increases have taken place in the annual number of hot days and warm nights for both Suva and Nadi in Fiji, with decreases in the annual number of cool days and cold nights at both locations. The number of hot days (max temperature ≥32 °C) shows a significant increasing trend while the number of colder nights (min temperature < 18 °C) showed a decreasing trend at Suva.…”
Section: Observed Changes In Climate Trends and Future Projectionsmentioning
confidence: 99%
“…1) weather stations reflect the climates of rainforests and TDF, with Suva in the wet, south-eastern rain forest zone and Nadi in the drier, western dry forest zone. The climatological observations of these two stations between 1961 and 2003 were detailed by Mataki et al (2006). while the annual average surface temperature is similar at both stations, Nadi receives considerably less average annual total rainfall (1810 mm) than Suva (3040 mm).…”
Section: Methods Climatementioning
confidence: 99%
“…1) and intercept the prevailing south-east tradewinds, creating rain shadows on the leeward side. as a result, a great variety of rainfall regimes exist in Fiji, ranging from about 1800 mm in the coastal regions of the western sides to 3000 mm and more on the south-eastern side (Mataki et al 2006). The wet, windward, south-eastern sides are covered with rainforest, while most of the dry, leeward, western sites are presently covered with grassland, called "talasiga" ("sunburnt land") in the native vernacular, and small forest remnants (parham 1972;MuellerDombois & Fosberg 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation